2009
DOI: 10.1016/j.pestbp.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea-resistant biotypes of Monochoria vaginalis generate higher ultraweak photon emissions than the susceptible ones

Abstract: All living organisms spontaneously generate ultraweak photon emissions, which originate from biochemical reactions in cells. Current research uses the ultraweak photon emission from organisms as a novel indicator in nondestructive analyses of an organisms living state. This study indicates that ultraweak photon emissions from Monochoria vaginalis are different between resistant biotypes (R) to sulfonulurea (SU) and susceptible biotypes (S). In SU-R biotypes, distinct increases in photon emissions were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Summarizing many years of work involving biophoton measurements, we have found that the collection of such data is a useful predictive tool, providing a routine means of distinguishing between stocks of seeds which would later show either high or low rates of seed germination. Predictive patterns of cellular light emission is a useful diagnostic tool in an agricultural context by way of identifying plant biotypes with differences in herbicide sensitivity (Inagaki et al 2009), as well as in the medical sciences (Takeda et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Summarizing many years of work involving biophoton measurements, we have found that the collection of such data is a useful predictive tool, providing a routine means of distinguishing between stocks of seeds which would later show either high or low rates of seed germination. Predictive patterns of cellular light emission is a useful diagnostic tool in an agricultural context by way of identifying plant biotypes with differences in herbicide sensitivity (Inagaki et al 2009), as well as in the medical sciences (Takeda et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the case of S. juncoides, this increment in biophoton emission in SU-resistant biotypes has been confirmed in Monochoria vaginalis [42]. Figure 7 shows the result of biophoton emissions after BSM treatment from leaf segments of four SU-resistant and four SU-susceptible biotypes of M. vaginalis [42]. In the four resistant biotypes, distinct increments were independent of differences in the mutation sites of the ALS genes.…”
Section: Biophoton Emissions In Su-resistant Plants Through Target-simentioning
confidence: 70%
“…Therefore, at this stage, there were no distinct differences in biophoton emissions between the resistant and susceptible biotypes [41]. In addition to the case of S. juncoides, this increment in biophoton emission in SU-resistant biotypes has been confirmed in Monochoria vaginalis [42]. Figure 7 shows the result of biophoton emissions after BSM treatment from leaf segments of four SU-resistant and four SU-susceptible biotypes of M. vaginalis [42].…”
Section: Biophoton Emissions In Su-resistant Plants Through Target-simentioning
confidence: 81%
“…Recently, field‐selected, SU‐resistant Monochoria vaginalis (a paddy weed) with an Ala 205 Val mutation was reported in a Japanese rice field (Inagaki et al . ). In addition, it was reported that new amino acid substitutions at Ala 122 , such as Ala 122 Val and Ala 122 Tyr, conferred high resistance to SU‐herbicides in upland weeds (Krysiak et al .…”
Section: Resultsmentioning
confidence: 97%
“…From field-selected, upland weeds that are resistant to ALS inhibitors, such as imidazolinones, mutations at the Ala 122 ,Ala 205 or Ser 653 site in the ALS gene are frequently reported, but they have not been regarded as conferring high (>10-fold) resistance to SU herbicides (Tranel & Wright 2002). Recently, field-selected, SU-resistant Monochoria vaginalis (a paddy weed) with an Ala 205 Val mutation was reported in a Japanese rice field (Inagaki et al 2009). In addition, it was reported that new amino acid substitutions at Ala 122 , such as Ala 122 Val and Ala 122 Tyr, conferred high resistance to SU-herbicides in upland weeds (Krysiak et al 2011;Han et al 2012).…”
mentioning
confidence: 99%